Prince of the People: The Life and Times of a Brazilian Free Man of Colour - Barman, Roderick J. (Labour / Le Travail, 1997)
The article reviews the book, "Prince of the People: The Life and Times of a Brazilian Free Man of Colour," by Eduardo Silva.
Keywords: BOOKS – Reviews; ETHNIC groups; Nonfiction; PRINCE of the People: The Life & Times of a Brazilian Free Man of Colour (Book); SILVA; Eduardo